Boosted top quarks and jet structure - Schätzel, Sebastian (The European physical journal. C, Particles and fields, 2015)
The Large Hadron Collider is the first particle accelerator that provides high enough energy to produce large numbers of boosted top quarks. The decay products of these top quarks are confined to a cone in the top quark flight direction and can be clustered into a single jet. Top quark reconstruction then amounts to analysing the structure of the jet and looking for subjets that are kinematically compatible with top quark decay. Many techniques have been developed in this context to identify top quarks in a large background of non-top jets. This article reviews the results obtained using data recorded in the years 2010-2012 by the experiments ATLAS and CMS. Studies of Standard Model top quark production and searches for new massive particles that decay to top quarks are presented.
Gesehen am 17.06.2020